PENGARUH IKLAN TERHADAP MINAT BELI DAN DAMPAKNYA TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK YAMAHA ALFA SCORPII PEKANBARU - Adlian Ichsan; Aida Nursanti; Tengku Firly Musfar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was conducted at PT. Yamaha Alpha Scorpii Pekanbaru. The purpose of this study was to determine the effect of advertising on buying interest on Yamaha products Alpha Scorpii Pekanbaru, to determine the influence of advertising on purchase decisions on Yamaha products Alpha Scorpii Pekanbaru and to determine the influence of advertising on purchasing decisions through buying interest on Yamaha products Alpha Scorpii Pekanbaru. To achieve these objectives the research performed by using the sample of 100 respondents, by using the method of data analysis that uses Partial Test. These results indicate that the effect of advertising and buying interest both positively and significantly on purchasing decisions on Yamaha products Alpha Scorpii Pekanbaru. In addition, the ad also significantly affect the buying interest. In the context of direct influence, interest in buying a higher effect of advertising on purchase decisions on Yamaha products Alpha Scorpii Pekanbaru.Keywords: Advertising, Interest, Purchasing, and Decision.